Examining the effects of Capital Structure on selected Companies listed on the Ghana Stock Exchange - Eduamah, Noble (2014)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the award of Master of Business Administration